Retention of technetium-99 by grout and backfill cements: Implications for the safe disposal of radioactive waste. (May 2020) - Isaacs, Matthew; Lange, Steve; Deissmann, Guido; Bosbach, Dirk; Milodowski, Antoni E.; Read, David
Abstract: Technetium-99 ( 99 Tc) is an important radionuclide when considering the disposal of nuclear wastes owing to its long half-life and environmental mobility in the pertechnetate (Tc(VII)) redox state. Its behaviour in a range of potential cement encapsulants and backfill materials has been studied by analysing uptake onto pure cement phases and hardened cement pastes. Preferential, but limited, uptake of pertechnetate was observed on iron-free, calcium silicate hydrates (C–S–H) and aluminate ferrite monosulphate (AFm) phases with no significant adsorption onto ettringite or calcium aluminates. Diffusion of 99 Tc through cured monolithic samples, representative of cements being considered for use in geological disposal facilities across Europe, revealed markedly diverse migration behaviour, primarily due to chemical interactions with the cement matrix rather than differential permeability or other physical factors. A backfill cement, developed specifically for the purpose of radionuclide retention, gave the poorest performance of all formulations studied in terms of both transport rates and overall technetium retention. Two of the matrices, pulverised fuel ash: ordinary Portland cement (PFA:OPC) and a low-pH blend incorporating fly ash, effectively retarded 99 Tc migration via precipitation in narrow, reactive zones. These findings have important implications when choosing cementitious grouts and/or backfill for Tc-containing radioactive wastes. Graphical abstract: Image 1 Highlights: Limited uptake of 99 Tc on C–S–H and AFm phases with no significant adsorption onto ettringite or calcium aluminates. Marked variation in diffusion of 99 Tc through cured cement monoliths due to chemical interactions with the cement matrix. Blends containing fly ash effectively retard 99 Tc migration via precipitation in narrow, reactive zones.